2005
DOI: 10.1002/mrd.20358
|View full text |Cite
|
Sign up to set email alerts
|

Developmental competence of porcine parthenogenetic embryos relative to embryonic chromosomal abnormalities

Abstract: Parthenogenetically activated (PA) embryos exhibit delayed development, a lower blastocyst rate, and less successful development in vitro compared to in vitro fertilized (IVF) embryos. To investigate the possible mechanisms for unsuccessful parthenogenetic development, this study analyzed the chromosome abnormalities and developmental potential of porcine PA embryos. Mature oocytes were electrically activated and cultured in Porcine Zygote Medium-3 (PZM3) supplemented with 3 mg/ml BSA for 6, 7, or 8 days. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Karyotype analysis showed that all HPs exhibited mixed ploidy, including haploid and diploid cells at the blastocyst stage 10, 11 , indicating that some haploid cells had already undergone self-diploidization before the blastocyst stage. Recently, advances in culture conditions and flow cytometric cell sorting have facilitated the derivation of embryonic stem cells (ESCs) from mammalian haploid parthenogenetic and androgenetic embryos 1215 .…”
Section: Introductionmentioning
confidence: 99%
“…Karyotype analysis showed that all HPs exhibited mixed ploidy, including haploid and diploid cells at the blastocyst stage 10, 11 , indicating that some haploid cells had already undergone self-diploidization before the blastocyst stage. Recently, advances in culture conditions and flow cytometric cell sorting have facilitated the derivation of embryonic stem cells (ESCs) from mammalian haploid parthenogenetic and androgenetic embryos 1215 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, karyotype analysis of parthenogenetic blastocysts derived from 2PB embryos by Hao et al (2006) [14] indicated that the rates of parthenogenetic embryos that have only haploid or diploid cells were over 40%, while the rate of mixoploid embryos having both haploid and diploid cells was only 7.7%. The reason for this discrepancy between our results and the results reported by Hao et al is not clear.…”
mentioning
confidence: 83%
“…However, parthenogenetic embryos that develop to the blastocyst stage typically have lower total cell numbers and poor developmental competence compared with fertilized embryos (Chen and Yu, ; Hao et al, ; Hardy and Handyside, ). Previous studies have shown that parthenogenetic embryos cannot develop to term in mammals due to abnormally imprinted Xist expression and failed X‐chromosome inactivation (Cruz et al, ; Liu et al, ; Park et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%